CULTURAL AND HERITAGE TRAIL TOURISM: STRENGTHENING LOCAL ECONOMY AND CULTURE RESOURCE CONSERVATION AT KOTAGEDE YOGYAKARTA - Wenang Anurogo; Muhammad Zainuddin Lubis; Condra Antroni; Novita Ayu Dewanti (SAMPURASUN, 2019)
The tourism industry is one of the sectors that can accelerate the economic movement in the region, so as to accelerate the growth and regional development. The benefits of the tourism industry at least able to improve the economic level of the tourist area. Kotagede Heritage Area is one of the main tourist destinations in Yogyakarta. Heritage trail tour activities that exist in the area of Kotagede is able to provide historical knowledge. The activity depends on the interest of the people and tourists in choosing tour packages. The research on heritage trail tourist object in Kotagede is using qualitative research method and combined with high-resolution remote sensing image data. The tourism of this Kotagede can be categorized into the resilience of community-based tourism areas in strengthening the local economy as well as and the preservation of cultural resources viewed from various aspects. The first aspect is the wage policy aspect given to the members of the cruise board, from which the youth who become tour guides can get income that can reduce the unemployment rate of the youth. The second aspect is in terms of trade, with the activity of tourism, the surrounding community who use to peddle traditional food to the modern will be a positive impact with the more their wares, especially if it is incorporated into one of the destinations of the tourist route. This aspect of trade can improve the welfare of the surrounding community by making it as a livelihood. The last aspect is the aspect of maintenance and rehabilitation of the infrastructure of the development area by private and government-related stakeholders. This can make the tourist area better and grow so as to increase the willingness of tourists to come to the place if the infrastructure is more compact.